2022
DOI: 10.1108/fs-10-2021-0200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive absorption on continuous use intention of AI-driven recommender systems in e-commerce

Abstract: Purpose The applications of artificial intelligence (AI), natural language processing and machine learning in e-commerce are growing. Recommender systems (RSs) are interaction-based technologies based on AI that can offer recommendations for products for use or of interest to a potential consumer. Curiosity, focused immersion and temporal dissociation are often treated as the dimensions of cognitive absorption, so exploring them separately can provide valuable insights into their dynamics. The paper aims to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The use of cutting-edge algorithms like CNN and CF diversifies sentiment analysis [38,61]. Ensemble classifiers like Random Forest [40,48] and hybrid systems like CNN-LSTM architectures [46,101,114] demonstrate purposeful integration of several techniques for sentiment analysis. Researchers believe this technological transition is a purposeful move from conventional methodologies to advanced integration of cutting-edge technology, notably in NLP and machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cutting-edge algorithms like CNN and CF diversifies sentiment analysis [38,61]. Ensemble classifiers like Random Forest [40,48] and hybrid systems like CNN-LSTM architectures [46,101,114] demonstrate purposeful integration of several techniques for sentiment analysis. Researchers believe this technological transition is a purposeful move from conventional methodologies to advanced integration of cutting-edge technology, notably in NLP and machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…This research adds significant contributions to the literature by empirically determining different influences of cognitive absorption and perceived usefulness on shoppers' intentions to reuse RSs. There has been little research on the impact of holistic consumer experience on behavioural intentions to reuse recommender systems [49], resulting in a lack of consensus, especially regarding the direct impact of the holistic consumer experience on behavioural intentions to reuse RSs. This research shows that a user's holistic experience, as measured by cognitive absorption, has a strong direct influence on behavioural intentions in the context of recommender systems.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive absorption in information technology refers to an individual's holistic experience and complete involvement with information technology [39,43,48,49]. It was initially seen as a trait but is now considered both a trait and a state [50].…”
Section: Cognitive Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saade et al [47] considered temporal dissociation, focused immersion, and heightened important enjoyment aspects of determining the individual intention to use online learning systems. Acharya et al [23] observed the direct effect of focused immersion and curiosity of continued intention to use. However, they observed no relationship between temporal dissociation and intention to use.…”
Section: Hypotheses 5a-cmentioning
confidence: 99%